Convergence of mathematical thinking and citizen science opportunities and challenges - Gonzales, Abigail B.
It is crucial for the public to develop their mathematical thinking, which is defined as a set of standard mathematical processes, specifically problem solving, reasoning & proof, communication, connections, and representation. Because citizen science is open for public participation, this study investigated the application of mathematical thinking in citizen science, including the opportunities and challenges that emerged in their convergence. Moreover, as citizen science is still unpopular in the Philippines, this study also investigated the difference between the citizen science projects from other countries and from the Philippines and provided improvements that can be employed by the projects based in the Philippines. Grounded theory approach was employed in this study and purposive sampling was used as a sampling method. Integrating the process of Charmaz (2006), the methodology of this study was as follows: (1) sorting the sample using a constructed criterion; (2) gathering of data; (3) qualitative coding; (4) initial coding; (5) focused coding and early memo-writing; (5) memo writing; (6) theoretical sampling; and (7) theoretical coding. Moreover, additional data were also collected during the initial and focused coding. The nature and scope of application of mathematical thinking was analyzed for each of the five clusters, namely Action, Conservation, Investigation, Virtual and Education, of citizen science projects determined by Wiggins and Crowston (2011) and in citizen science as a whole. Result shows that citizen science has a sufficient depth of application of mathematical thinking, has relatively varied combinations of mathematical processes and has a sufficient scope of application of mathematical thinking. Moreover, the result shows that the nature of application of mathematical thinking, that is the depth and the variation of the combinations of mathematical thinking processes, in Philippine-based citizen science projects were comparable with citizen science from other countries. However, the scope of Philippine-based citizen science projects was more limited than the scope from the other countries. In addition to that, this study theorized about the comprehensiveness of the application of mathematical thinking in citizen science. According to this theory, if a citizen science project (i) assigns primary tasks to its citizen scientists that require execution of multiple mathematical thinking process and multiple subcomponents of the mathematical thinking processes, (ii) delegates primary tasks that require performing different integrated or combined mathematical thinking processes, (iii) and designates numerous and diverse phases of participation to citizen scientists, then the citizen science project provides comprehensive application of mathematical thinking for their citizen scientists. Hence, it is recommended that students, educators, parents, and other education stakeholders participate in on-going and accessible citizen science projects as it provides opportunities for their citizen scientists to develop their own mathematical thinking. Moreover, the theory on the comprehensiveness of the application of mathematical thinking in citizen science is recommended to be used by the project leaders of citizen science projects in planning and improving their projects and by educators in assessing their prospect-citizen science projects.